Jakie prawo jest potrzebne pedagogom? - Andrzejewski , Marek (Studia Edukacyjne, 2017)
The article discusses the relation between law and pedagogy as well as between lawyers (theoreticians and practitioners) and pedagogues (theoreticians and practitioners). The author describes the manifestations of the current legal crisis and indicates how this process affects social life, particularly its pedagogical aspect. In his opinion, law should ensure freedom of pedagogical initiatives instead – as the dominant trend dictates – restrain them. The article is a changed version of a lecture delivered on the occasion of a jubilee of Professor Wiesław Ambrozik, held on 16 November 2017, in Collegium Minus, Adam Mickiewicz University, Poznań.